A naphthalimide-based fluorescent probe for highly selective detection of histidine in aqueous solution and its application in in vivo imaging. Issue 15 (21st January 2015) - Un, Hio-Ieng; Wu, Shuai; Huang, Chang-Bo; Xu, Zheng; Xu, Lin
Abstract : A naphthalimide-based fluorescent probe for selectively detecting His in aqueous solution, living cells, and C. elegans has been developed. Abstract : A naphthalimide-based fluorescent ensemble probe NPC for selectively detecting His in aqueous solution (10 mM HEPES, pH 7.4) has been reported. Moreover, the application of NPC in in vivo (both in Hela cells and in C. elegans ) fluorescence imaging was carried out as well.